Modelling and simulation of voltage source converter with different control technique for offshore windfarm application - Romlan, Afiq Asyraf (IRC, 2014)

(untitled)
The uses of Voltage Source Converter is not something new in wind farm power generation. Advance technologies in rebuilding VSC that can control the output of alternating current (AC) through several current control technique produces from the wind energy, sometime lead to distortion that can disturb another component whether in VSC itself or effecting another equipment. In wind farm power generation, power VSC commonly used in order to deal with large value of voltage and current produced from wind energy. Hence, more electronic device and components will be used to deal with this situation. This is to some extent will create disturbances to the system that will not be seen through human naked eye. Through this paper, a conventional current control method, that is linear PWM is present. This method is much more complicated compare to proposed method, that is predictive current control. The function of multi predictive control (MPC) in determining the future value for the feedback signal into inverter is explained in 4.3. The result of this two method is analyse in aspect of total harmonic distortion (THD) for both voltage and current during transient state and steady state. During transient state for current, both of the methods exceed the IEEE-519 standards. Hence it is recommend to install several equipments to protect the facility of windfarm itself. While for steady state, both of the methods succeed maintain the THD below 5% for voltage and current.